2022
DOI: 10.1101/2022.05.23.493040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rates and spectra of de novo structural mutation in Chlamydomonas reinhardtii

Abstract: Genetic variation originates from several types of spontaneous mutation, including single nucleotide substitutions, short insertions and deletions (INDELs), and larger structural changes. Structural mutations (SMs) drive genome evolution and are thought to play major roles in evolutionary adaptation, speciation and genetic disease, including cancers. Sequencing of mutation accumulation (MA) lines has provided estimates of rates and spectra of single nucleotide and INDEL mutations in many species, yet the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Recent work has in fact demonstrated that an unexpectedly large proportion of mutations in Chlamydomonas are beneficial under laboratory conditions, potentially due to many genes being dispensable in such an artificial environment (Böndel et al 2019;Böndel et al 2022). It has also been estimated that ~5-10% of all de novo mutations in Chlamydomonas experimental lines are >50 bp (López-Cortegano et al 2022), supporting a prominent role for structural evolution in the laboratory. The implications of "laboratory domestication" have been considered in other model systems such as Caenorhabditis elegans (Sterken et al 2015), and laboratory mutations should be carefully considered when evaluating experimental results.…”
Section: The Present and Future Of The Chlamydomonas Genome Projectmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent work has in fact demonstrated that an unexpectedly large proportion of mutations in Chlamydomonas are beneficial under laboratory conditions, potentially due to many genes being dispensable in such an artificial environment (Böndel et al 2019;Böndel et al 2022). It has also been estimated that ~5-10% of all de novo mutations in Chlamydomonas experimental lines are >50 bp (López-Cortegano et al 2022), supporting a prominent role for structural evolution in the laboratory. The implications of "laboratory domestication" have been considered in other model systems such as Caenorhabditis elegans (Sterken et al 2015), and laboratory mutations should be carefully considered when evaluating experimental results.…”
Section: The Present and Future Of The Chlamydomonas Genome Projectmentioning
confidence: 96%
“…MSAT-11_cRei arrays consist of a 1.9 kb tandemly repeated monomer and are present on chromosomes 7 and 12 in all three available genomes, with two additional unique insertions in CC-1690 (not shown). Similarly, MSAT-11_cRei de novo insertions have recently been observed in experimental lines of the field isolate CC-2931(López-Cortegano et al 2022. There are very few observations of de novo satellite dissemination and its mechanisms are generally unclear (Ruiz-Ruano et al 2016), although rolling circle replication and reinsertion via extrachromosomal circular DNA intermediates has been proposed (Navrátilová et al 2008).…”
Section: Cc-4532 Also Carries Structural Mutationsmentioning
confidence: 98%
“…Recent work has in fact demonstrated that an unexpectedly large proportion of mutations in Chlamydomonas are beneficial under laboratory conditions, potentially due to many genes being dispensable in such an artificial environment (Böndel et al 2019; Böndel et al 2022). It has also been estimated that ∼5-10% of all de novo mutations in Chlamydomonas experimental lines are >50 bp (López-Cortegano et al 2022), supporting a prominent role for structural evolution in the laboratory. The implications of “laboratory domestication” have been considered in other model systems such as Caenorhabditis elegans (Sterken et al 2015), and laboratory mutations should be carefully considered when evaluating experimental results.…”
Section: Resultsmentioning
confidence: 97%
“…Still, the mutation rates of structural variants, especially complex ones such as inversions, remain difficult to measure. The emergence of long-read sequencing technologies, such as circular consensus sequencing of single molecules up to tens of kilobases, may shed new light on mutation rates of complex structural variants and transposable element dynamics (66,75).…”
Section: Mutation Rates In the Molecular Agementioning
confidence: 99%